PENYULUHAN DAN KONSELING METODE KONTRASEPSI JANGKA PANJANG PADA WANITA USIA SUBUR DI KELURAHAN TALANG JAMBE PALEMBANG - Rohani, Rohani; Oktaria, Dina (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2021)
The Long-term contraceptive method, abbreviated as MKJP, is a method of contraception that is known to be effective because it can provide protection from the risk of pregnancy for a period of up to ten years consisting of the Female Operation Method (FOM), the Male Operation Method (MOP), and the intrauterine device (IUD). and implants or what is known as implant KB is a contraceptive device under the skin with a validity period of three years. The method used to achieve the target of this activity is by way of approach, counseling, and free counseling services. Thus the community will get services through a series of activities that support the improvement of the quality of public health and education, of course. The final output of this activity is that women of childbearing age in the Talang Jambe village of Palembang are able to understand long-term contraceptive methods. And of course, after counseling and counseling services for women of childbearing age and becoming active family planning acceptors with long-term contraceptive methods.